Investigations for tensile, compressive and morphological properties of 3D printed functional prototypes of PLA-PEKK-HAp-CS. (October 2021) - Singh, Rupinder; Singh, Gurchetan; Singh, Jaskaran; Kumar, Ranvijay
This article reports the experimental investigations for tensile, compressive and morphological properties of 3D printed functional prototypes composed of polylactic acid (PLA) reinforced with poly ether ketone ketone (PEKK), hydroxyapatite (HAp) and chitosan (CS). The PLA-PEKK-HAp-CS composite has wide applications as scaffolds in orthopaedics and clinical dentistry. The tensile and compressive specimens were printed (as per ASTM D638 type IV and ASTM D695) with in-house prepared feedstock filament on commercial fused deposition modelling setup by following Taguchi-based design of experiment. The results are also supported by hardness data and photomicrographs.